Direct immunofluorescence in cutaneous vasculitis: Experience from a referral hospital in India - B N Nandeesh; Rajalakshmi Tirumalae (Wolters Kluwer Medknow Publications, 2013)
Background : Cutaneous vasculitis is commonly recognized and biopsied, owing to ease of access. Most biopsies are also subjected to direct immunofluorescence (DIF), though the rates of positivity vary. This is an attempt to assess the utility of DIF and glean data that will help optimize the test. Objective : To assess the diagnostic utility of DIF in cutaneous vasculitis. Materials and Methods : All cases of suspected cutaneous vasculitis submitted for DIF between 2004 and 2010 were included. Clinical data, histopathologic diagnosis, DIF findings and additional tests such as anti nuclear antibody (ANA), anti neutrophil cytoplasmic antibody (ANCA) (where done) were noted. Results: There were 198 patients in the study group, with a female predominance. Purpura was the commonest clinical presentation. Extracutaneous involvement was noted in 29% of patients' i.e., joint pain, abdominal pain and hematuria. Leukocytoclastic vasculitis was the commonest histologic diagnosis. DIF showed an overall positivity of 39% (n = 77) with C3 in 26% (n = 52) and IgA in 23% (n = 46) cases. Forty one cases of suspected Henoch Schonlein Purpura (HSP) showed IgA positivity. The timing of biopsy ranged from <3 days to six months, with 38% being done within seven days. DIF was positive in 86% of biopsies performed within seven days of onset of lesions. Sixty percent of patients with extracutaneous manifestations showed deposits. Vascular deposits were also noted in dermatitis herpetiformis, dematomyositis and prurigo. Conclusion : DIF positivity is strongly influenced by the timing of the biopsy and the presence of extracutaneous features. Its clinical value is greatest in patients with HSP, being contributory in 90% of cases. Vascular deposits may be seen in non-vasculitic conditions and need clinicopathologic correlation.